Respostas

2013-08-07T21:24:03-03:00
Tc = TF - 32 ---> Tc = Tc - 32 => tc9 = 5(tc - 32) --> 9tc = 5tc - 160 --> 9tc - 5tc = -160
5          9               5         9                                                                       4tc = - 160
                                                                                                                   tc = -160 = -40
                                                                                                                            4